Solid-state battery positive electrode material and preparation method and application thereof

By adding a forming additive with a friction coefficient of 0.001 to 0.3 to the positive electrode material of the solid-state battery, the problem of poor solid contact on the positive electrode side of the solid-state battery is solved, and more stable battery performance and higher volume energy density are achieved.

CN119833567APending Publication Date: 2025-04-15SHANGHAI JIAOTONG UNIV TECH TRANSFER CENT CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411844870.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The solid contact between the active particles on the positive electrode side and the electrolyte particles at low external pressure is poor, resulting in battery circulation attenuation and increased internal voids, limiting the actual application of the battery.

Method used

A molding additive with a friction coefficient of 0.001 to 0.3 is used as a component of the positive electrode material, and mixing it with the positive electrode active material, a solid electrolyte and a conductive agent to form a positive electrode material that improves solid contact and reduces internal voids.

Benefits of technology

It effectively enhances the solid contact of the positive electrode of the solid-state battery, reduces the internal void ratio, improves the cycling performance and volume energy density of the battery, reduces the operating pressure, and achieves stable battery performance under low external pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833567A_ABST
    Figure CN119833567A_ABST
Patent Text Reader

Abstract

The invention discloses a solid-state battery positive electrode material as well as a preparation method and application thereof. The positive electrode material comprises the following raw materials: a positive electrode active material, a solid-state electrolyte, a conductive agent, a binder and a forming aid with a friction coefficient of 0.001-0.3, during preparation, the positive electrode active material, the solid electrolyte and the conductive agent are mixed for the first time and uniformly ground, then the molding aid is added for second mixing, then the binder is added for third mixing, and compression molding is performed to obtain the positive electrode material. The positive electrode material provided by the invention has relatively high compaction density and low porosity after film formation, can realize stable solid-solid contact, can construct a stable electron and ion network path, improves the volume energy density of the whole electrode, and improves the conductivity of the electrode. The solid-state battery assembled by using the solid-state battery positive electrode material can have high specific capacity exertion and stable cycle performance under low external pressure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and in particular to a solid-state battery positive electrode material and a preparation method and application thereof. Background Art

[0002] Solid-state batteries have attracted much attention due to their high theoretical energy density, high safety performance and longer cycle life. Compared with traditional liquid lithium batteries, all-solid-state batteries use solid electrolytes instead of flammable liquid electrolytes, and also have the function of diaphragms, which increases the safety of the battery. As one of the core components, solid electrolytes have developed rapidly in recent years, including sulfide solid electrolytes, halide solid electrolytes, polymer solid electrolytes, oxide solid electrolytes, etc. Their conductivity is almost comparable to that of liquid electrolytes. However, since solid electrolytes are solid, there is solid-solid contact between the active particles and the electrolyte particles on the positive electrode side, the interface impedance is large, and ion or electron transmission is difficult. Therefore, when the battery is running, a very high pressure needs to be applied to ensure the close solid-solid contact. The high operating pressure limits the practical application of all-solid-state batteries; however, the solid-solid contact of the all-solid positive electrode is worse under low external pressure, which is an important reason for the battery cycle attenuation. Not only that, the volume change of the active particles during the low external pressure cycle also increases the internal voids of the positive electrode, further exacerbating the problem of solid-solid contact failure. Summary of the invention

[0003] The object of the present invention is to overcome one or more deficiencies in the prior art and to provide an improved solid-state battery positive electrode material that can at least enhance solid-solid contact and reduce internal voids.

[0004] The present invention also provides a method for preparing the above-mentioned solid-state battery positive electrode material and its application in preparing solid-state batteries.

[0005] In order to achieve the above object, a technical solution adopted by the present invention is:

[0006] A solid-state battery positive electrode material, the raw materials of which include a positive electrode active material, a solid electrolyte, a conductive agent, a binder, and a molding aid with a friction coefficient of 0.001 to 0.3.

[0007] In some embodiments of the present invention, the friction coefficient of the molding aid is 0.005 to 0.20. Further, the friction coefficient of the molding aid is 0.005 to 0.15.

[0008] According to some preferred and specific aspects of the present invention, the friction coefficient of the molding aid is 0.01 to 0.05.

[0009] In the present invention, the friction coefficient of the molding aid is measured by the following method (the testing instrument is LANBO MXZ-1 friction coefficient tester):

[0010] The molding aid was pressed into a disc with a diameter of 12 mm at 300 MPa, and then placed on a horizontal iron block. A 20 kg weight was placed on the disc, and then a force F was applied in the horizontal direction to drag the disc. The friction coefficient was calculated by the following formula:

[0011] μ=F(m) / F(positive)

[0012] Where: μ is the friction coefficient; F(f) is the friction force, which is equivalent to the applied force F; F(positive) is the positive force (normal force), that is, the weight of the 20kg weight.

[0013] In some embodiments of the present invention, the molding aid accounts for 0.1% to 10% of the raw material of the positive electrode material by weight percentage; further, the molding aid accounts for 0.5% to 5% of the raw material of the positive electrode material by weight percentage.

[0014] In some embodiments of the present invention, the molding aid comprises a combination of one or more selected from polytetrafluoroethylene powder, magnesium stearate, calcium stearate, polyacrylonitrile, microcrystalline cellulose, wax powder and polyvinylidene fluoride powder.

[0015] In some embodiments of the present invention, the molecular weight of the polytetrafluoroethylene powder is 10,000 to 600,000, and the particle size is 0.01 to 100 microns. Further, the molecular weight of the polytetrafluoroethylene powder is 50,000 to 300,000, and the particle size is 0.2 to 10 microns.

[0016] In some embodiments of the present invention, the particle size of the magnesium stearate is 1 to 20 microns; further, the particle size of the magnesium stearate is 1 to 5 microns.

[0017] In some embodiments of the present invention, the limiting degree of polymerization of the microcrystalline cellulose is 100-500, and the particle size is 1-100 microns; further, the limiting degree of polymerization of the microcrystalline cellulose is 200-400, and the particle size is 1-20 microns; further, the limiting degree of polymerization of the microcrystalline cellulose is 250-350, and the particle size is 1-10 microns.

[0018] In some embodiments of the present invention, the molecular weight of the wax powder is 1,000 to 100,000, and the particle size is 800-6000 mesh. Further, the molecular weight of the wax powder is 8000-30000, and the particle size is 1000-3000 mesh.

[0019] In some embodiments of the present invention, the molecular weight of the polyvinylidene fluoride powder is 10,000 to 100,000, and the particle size is 0.2 to 20 microns; further, the molecular weight of the polyvinylidene fluoride powder is 50,000 to 150,000, and the particle size is 0.5 to 10 microns.

[0020] In some embodiments of the present invention, the particle size of the calcium stearate is 0.5-5 microns.

[0021] In some embodiments of the present invention, the molecular weight of the polyacrylonitrile is 50,000 to 300,000, and the particle size is 1 to 20 microns.

[0022] In some embodiments of the present invention, the addition form of the molding aid includes a powder form or a dispersion form, and the dispersion form is formed by dispersing the molding aid in powder form in a solvent. The solvent can be water and / or an organic solvent, and the organic solvent can include 1,2-dimethoxyethane, tetrahydrofuran, toluene, etc.

[0023] In some embodiments of the present invention, the positive electrode active material includes a combination of one or more selected from nickel cobalt lithium manganese oxide ternary positive electrode materials, lithium manganese oxide positive electrode materials, lithium cobalt oxide positive electrode materials, nickel manganese oxide positive electrode materials, lithium nickel oxide positive electrode materials, nickel cobalt aluminum oxide ternary positive electrode materials, nickel cobalt manganese aluminum quaternary positive electrode materials, lithium manganese-rich based positive electrode materials and lithium iron phosphate positive electrode materials.

[0024] The present invention does not specifically limit the solid electrolyte. As long as it is a solid electrolyte, there is a large interface impedance between the active particles on the positive electrode side, such as solid-solid contact, and ion or electron transmission is difficult. Therefore, a very high pressure needs to be applied during battery operation to ensure close solid-solid contact. High operating pressure limits the practical application of all-solid-state batteries; however, the solid-solid contact of all-solid positive electrodes is worse under low external pressure. The present invention is an improvement based on this problem.

[0025] In some embodiments of the present invention, the solid electrolyte comprises a combination of one or more selected from a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte and a polymer solid electrolyte;

[0026] Furthermore, the oxide solid electrolyte includes one or more combinations selected from LiPON and its homologues, LLZTO and its homologues, LATP and its homologues; the sulfide solid electrolyte includes one or more combinations selected from LGPS and its homologues, LiPSCl and its homologues, β-Li3PS4 and its homologues, Li7P3S 11 and its homologues, Li 10 GeP2S 12and its homologues and a combination of one or more of Li6PS5X and its homologues, X is Cl, Br or I; the halide solid electrolyte includes a combination of one or more selected from Li3InCl6 and its homologues, Li3YCl6 and its homologues.

[0027] In the present invention, the "homologous series" of the solid electrolyte refers to compounds having the same elemental composition but with different atomic ratios of the elements in the solid electrolyte.

[0028] In some embodiments of the present invention, the conductive agent includes conductive carbon powder, and the conductive carbon powder includes a combination of one or more selected from carbon black, conductive graphite, carbon fiber (VGCF), carbon nanotube (CNT) and graphene.

[0029] In some embodiments of the present invention, the molecular weight of the binder is 800,000 to 10 million; further, the molecular weight of the binder is 2 million to 5 million.

[0030] In some embodiments of the present invention, the viscosity of the binder is 100 to 8000 cps; further, the viscosity of the binder is 1000 to 5000 cps.

[0031] In some embodiments of the present invention, the binder includes a combination of one or more selected from polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyphthalamide (PPA), polyamideimide (PAI), polyvinyl alcohol (PVA), polyetherimide (PEI), and polyimide (PI).

[0032] In some embodiments of the present invention, the binder accounts for 0.01% to 10% of the raw material of the positive electrode material by weight. Further, the binder accounts for 0.05% to 5% of the raw material of the positive electrode material by weight.

[0033] In some embodiments of the present invention, the particle size of the solid electrolyte is 0.1 to 20 microns; further, the particle size of the solid electrolyte is 0.1 to 5 microns.

[0034] According to a specific aspect of the present invention, the D 50 =0.1~1.5μm.

[0035] In some embodiments of the present invention, the solid electrolyte accounts for 5% to 45% of the raw material of the positive electrode material by mass percentage; further, the solid electrolyte accounts for 10% to 35% of the raw material of the positive electrode material by mass percentage.

[0036] In some embodiments of the present invention, the positive electrode active material accounts for 50% to 90% of the raw material of the positive electrode material by mass percentage; further, the positive electrode active material accounts for 60% to 85% of the raw material of the positive electrode material by mass percentage.

[0037] In some embodiments of the present invention, the conductive agent accounts for 1% to 40% of the raw material of the positive electrode material by mass percentage; further, the conductive agent accounts for 2% to 20% of the raw material of the positive electrode material by mass percentage.

[0038] Another technical solution provided by the present invention is a method for preparing the above-mentioned solid-state battery positive electrode material, the preparation method comprising:

[0039] The positive electrode active material, the solid electrolyte and the conductive agent are mixed for the first time, and after being ground evenly, a molding aid is added for the second mixing, and then a binder is added for the third mixing, and the mixture is pressed and molded to obtain the solid-state battery positive electrode material.

[0040] In some embodiments of the present invention, when the molding aid is added in the form of a dispersion, it can be dried in advance to obtain a powder form and then mixed, or the molding aid in the form of a dispersion can be directly added to the system, mixed and dried.

[0041] In some embodiments of the present invention, the first mixing, the second mixing, and the third mixing can all be dry mixing.

[0042] The present invention mixes the positive electrode active material, solid electrolyte and conductive agent for the first time to ensure the uniform dispersion of the three, the positive electrode active material, solid electrolyte and conductive agent; then adds a molding aid for the second mixing, the addition of which can reduce the porosity of the solid positive electrode after being pressed into a film, reduce the amount of solid electrolyte used, and thus increase the amount of positive electrode active material. Then, a binder is added for the third mixing and pressed into a film, which can further reduce the porosity of the all-solid positive electrode and increase the compaction density.

[0043] In some embodiments of the present invention, the compression molding is performed at a temperature of 20 to 200° C. and a pressure of 100 to 1000 MPa; further, at a temperature of 30 to 100° C. and a pressure of 300 to 500 MPa.

[0044] Another technical solution provided by the present invention is: a solid-state battery, comprising a positive electrode sheet, wherein the positive electrode sheet comprises the solid-state battery positive electrode material described above.

[0045] Furthermore, the operating pressure of the solid-state battery is less than 50 MPa, further less than 30 MPa, and further 1 to 10 MPa.

[0046] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0047] The inventors of the present invention have found in a large number of experimental studies that by adding a molding aid having a friction coefficient of 0.001 to 0.3 in the positive electrode material to a composite positive electrode material system including a positive electrode active material and a solid electrolyte, the problem of poor solid-solid contact between active particles and electrolyte particles under low external pressure can be effectively improved or even solved, which helps to reduce the porosity caused by the volume change of active particles during the low external pressure cycle.

[0048] Furthermore, the positive electrode material of the present invention has a relatively high compaction density and low porosity after film formation, which can achieve stable solid-solid contact, construct a stable electron and ion network pathway, improve the volume energy density of the entire electrode, and reduce the stress and strain of the entire positive electrode during the cycle, thereby improving the cycle performance of the battery. The solid-state battery assembled with this solid-state battery positive electrode material can have a high specific capacity and stable cycle performance under low external pressure, providing a solution for achieving stable operation under low pressure and improving the overall volume energy density of the all-solid-state battery; it also provides a possible solution to the problem of large strain during the subsequent large-stack all-solid-state battery cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.

[0050] Figure 1 This is a schematic diagram of the interior of the positive electrode of the all-solid-state battery after adding a molding aid and pressing into a film in an embodiment of the present invention;

[0051] Figure 2 This is a schematic diagram of the interior of the positive electrode of the all-solid-state battery that is pressed into a film without adding a molding aid in Comparative Example 1 of the present invention;

[0052] Figure 3 This is a schematic diagram of the structure of an all-solid-state mold half-cell in an embodiment of the present invention;

[0053] Figure 4 The graphs are cycle performance test diagrams of all-solid-state mold half-cells prepared using the positive electrodes obtained in the embodiments of the present invention and the comparative examples, respectively. DETAILED DESCRIPTION

[0054] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0055] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.

[0056] In the following, the positive electrode active material is a single crystal NCM811 positive electrode material;

[0057] Sulfide solid electrolyte is Li6PS5Cl, D 50 =0.6μm;

[0058] The conductive agent is VGCF, purchased from CLUDE, brand number MA-EN-CO-000901;

[0059] The binder is PTFE, with a molecular weight of about 5 million and a viscosity of about 2000 cps, purchased from Daikin Fluorochemical, brand 104;

[0060] Polytetrafluoroethylene micropowder, with a friction coefficient of about 0.02, a molecular weight of about 100,000, and a particle size of about 0.5 μm, was purchased from Daikin Fluorochemicals, brand L-5F;

[0061] Magnesium stearate, with a friction coefficient of about 0.28 and a particle size of about 3 μm, was purchased from Zhongtai Lianhua, brand AG-505;

[0062] Calcium stearate, with a friction coefficient of about 0.25 and a particle size of about 1 micron, was purchased from Sigma Aldrich, brand 26411;

[0063] Microcrystalline cellulose, with a friction coefficient of about 0.12, a limiting degree of polymerization of about 300, and a particle size of about 5 μm, was purchased from Sinopharm Reagent, brand number 68005761;

[0064] Wax powder, with a friction coefficient of about 0.11, a molecular weight of about 10,000, and a particle size of about 2000 mesh, was purchased from Chengxin Plastics, brand 7310P;

[0065] Wax emulsion, purchased from Nanjing Tianshi New Material Technology Co., Ltd., brand 0E-6201N;

[0066] Polyvinylidene fluoride micropowder, with a friction coefficient of about 0.13, a molecular weight of about 100,000, and a particle size of about 5 microns, purchased from Arkema, brand 10w PVDF;

[0067] Polyacrylonitrile, with a friction coefficient of about 0.3, a molecular weight of about 150,000, and a particle size of about 3 microns, was purchased from Sigma Aldrich, brand 181315.

[0068] Embodiment 1:

[0069] This example provides a solid-state battery positive electrode material and a preparation method thereof, the preparation method comprising: mixing single crystal NCM811 and sulfide solid electrolyte D 50 = 0.6 μm and VGCF were first dry mixed for 20 minutes and ground evenly. Then polytetrafluoroethylene micro powder molding aid was added for the second dry mixing, and then PTFE binder was added for the third dry mixing, and pressed to form a solid-state battery positive electrode material (referred to as all-solid-state positive electrode A);

[0070] Among them, the mass ratio of NCM811, sulfide solid electrolyte, VGCF, polytetrafluoroethylene powder and PTFE binder is 7:3:0.5:0.2:0.1;

[0071] The press molding was performed at a temperature of 60° C. and a pressure of 600 MPa.

[0072] Embodiment 2:

[0073] This example provides a solid-state battery positive electrode material and a preparation method thereof, which is basically the same as Example 1, and the only difference is that the "polytetrafluoroethylene micropowder molding aid" is replaced with an equal amount of "magnesium stearate".

[0074] Embodiment 3:

[0075] This example provides a solid-state battery positive electrode material and a preparation method thereof, which is basically the same as Example 1, and the only difference is that the "polytetrafluoroethylene micropowder molding aid" is replaced with an equal amount of "microcrystalline cellulose".

[0076] Embodiment 4:

[0077] This example provides a solid-state battery positive electrode material and a preparation method thereof, which is basically the same as Example 1, and the only difference is that the "polytetrafluoroethylene micropowder molding aid" is replaced with an equal amount of "wax powder".

[0078] Embodiment 5:

[0079] This example provides a solid-state battery positive electrode material and a preparation method thereof, which is basically the same as Example 1, and the only difference is that the "polytetrafluoroethylene micropowder molding aid" is replaced with an equal amount of "polyvinylidene fluoride micropowder".

[0080] Embodiment 6:

[0081] This example provides a solid-state battery positive electrode material and a preparation method thereof, which is basically the same as Example 1, except that the mass ratio of NCM811, sulfide solid electrolyte, VGCF, polytetrafluoroethylene powder and PTFE binder is 7:3:0.5:0.1:0.1.

[0082] Embodiment 7:

[0083] This example provides a solid-state battery positive electrode material and a preparation method thereof, which is basically the same as Example 1, with the only difference being that the mass ratio of NCM811, sulfide solid electrolyte, VGCF, polytetrafluoroethylene powder and PTFE binder is 7:3:0.5:0.5:0.1.

[0084] Embodiment 8:

[0085] This example provides a solid-state battery positive electrode material and a preparation method thereof, which is basically the same as Example 1, and the only difference is that the "polytetrafluoroethylene micropowder molding aid" is replaced with an equal amount of "calcium stearate".

[0086] Embodiment 9:

[0087] This example provides a solid-state battery positive electrode material and a preparation method thereof, which is basically the same as Example 1, and the only difference is that the "polytetrafluoroethylene micropowder molding aid" is replaced with an equal amount of "polyacrylonitrile".

[0088] Embodiment 10:

[0089] This example provides a solid-state battery positive electrode material and a preparation method thereof, which is basically the same as Example 4, except that the wax powder is replaced with a wax emulsion. The preparation method includes: single crystal NCM811 and sulfide solid electrolyte D 50 =0.6μm and VGCF were mixed for 20 minutes and ground evenly. Then wax emulsion was added for mixing, homogenized for 20 minutes, the solvent was evaporated at 80°C in vacuum, and finally PTFE binder was added for mixing, pressed and formed to make a solid-state battery positive electrode material; wherein the mass ratio of NCM811, sulfide solid electrolyte, VGCF, wax emulsion (calculated by solid content) and PTFE binder was 7:3:0.5:0.2:0.1.

[0090] Comparative Example 1:

[0091] This example provides a solid-state battery positive electrode material and a preparation method thereof, which is basically the same as Example 1, except that no polytetrafluoroethylene micropowder molding aid is added.

[0092] Performance Testing:

[0093] The positive electrode materials obtained in the above examples 1-10 and comparative example 1 were subjected to electrical performance tests, as follows: The test equipment used in the test includes: Shenzhen Xinwei charge and discharge tester, biologicVP3, thickness measuring instrument. The test items involved in the test include: Electrical performance evaluation of all-solid-state positive electrode All-solid-state mold half-cell assembly: Li6PS5Cl (LPSC) is used as the solid electrolyte, Li-In alloy is used as the negative electrode, stainless steel sheet is used as the current collector, the inner diameter of the solid mold is 10mm, and the schematic diagram of the all-solid-state mold half-cell structure is as shown Figure 3 As shown. The specific steps are: first, weigh 100 mg of sulfide solid electrolyte in a solid mold, flatten it and press it at 1.5T pressure for 2 minutes, then put the all-solid composite positive electrode with a diameter of 10 mm from the top of the mold, add a stainless steel sheet (diameter of 10 mm), and then press it at 2.5T pressure for 1 minute, then put an indium sheet with a diameter of 10 mm, a lithium sheet with a diameter of 6 mm, and a stainless steel sheet with a diameter of 10 mm from the bottom of the mold in turn, and finally press it at 5T pressure for 1 minute to obtain an all-solid mold half-cell. Note: A pressure of 10MPa needs to be applied to the all-solid mold half-cell during the test.

[0094] The test data is shown in Table 1.

[0095] Table 1

[0096]

[0097] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0098] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A solid-state battery positive electrode material, characterized in that: The raw materials of the positive electrode material include positive electrode active material, solid electrolyte, conductive agent, binder, and molding auxiliary agent with a friction coefficient of 0.001 to 0.

3.

2. The solid-state battery positive electrode material according to claim 1, characterized in that: The friction coefficient of the molding aid is 0.005 to 0.20; and / or, in terms of mass percentage, the molding aid accounts for 0.1% to 10% of the raw material of the positive electrode material.

3. The solid-state battery positive electrode material according to claim 2, characterized in that: The friction coefficient of the molding aid is 0.005 to 0.15; and / or, in terms of mass percentage, the molding aid accounts for 0.5% to 5% of the raw material of the positive electrode material.

4. The solid-state battery positive electrode material according to claim 3, characterized in that: The friction coefficient of the molding aid is 0.01 to 0.

05.

5. The solid-state battery positive electrode material according to claim 1, characterized in that: The molding aid comprises one or more combinations selected from polytetrafluoroethylene micropowder, magnesium stearate, calcium stearate, polyacrylonitrile, microcrystalline cellulose, wax powder and polyvinylidene fluoride micropowder.

6. The solid-state battery positive electrode material according to claim 5, characterized in that: The molecular weight of the polytetrafluoroethylene micropowder is 10,000 to 600,000, and the particle size is 0.01 to 100 microns; and / or, the particle size of the magnesium stearate is 1 to 10 microns; and / or, the limiting degree of polymerization of the microcrystalline cellulose is 100 to 500, and the particle size is 1 to 100 microns; and / or, the molecular weight of the wax powder is 10,000 to 100,000, and the particle size is 800-6000 mesh; and / or, the molecular weight of the polyvinylidene fluoride micropowder is 10,000 to 200,000, and the particle size is 0.2 to 20 microns; and / or, the particle size of the calcium stearate is 0.5 to 5 microns; and / or, the molecular weight of the polyacrylonitrile is 50,000 to 300,000, and the particle size is 1 to 20 microns.

7. The solid-state battery positive electrode material according to claim 6, characterized in that: The molecular weight of the polytetrafluoroethylene micropowder is 50,000 to 300,000, and the particle size is 0.2 to 10 microns; and / or the particle size of the magnesium stearate is 1 to 5 microns; and / or the molecular weight of the wax powder is 8000-30000, and the particle size is 1000-3000 mesh; and / or the limiting degree of polymerization of the microcrystalline cellulose is 200 to 400, and the particle size is 1 to 20 microns; and / or the molecular weight of the polyvinylidene fluoride micropowder is 50,000 to 150,000, and the particle size is 0.5 to 10 microns.

8. The solid-state battery positive electrode material according to any one of claims 1 to 7, characterized in that: The addition form of the molding aid includes a powder form or a dispersion form, and the dispersion form is formed by dispersing the molding aid in powder form in a solvent.

9. The solid-state battery positive electrode material according to claim 1, characterized in that: The positive electrode active material includes a combination of one or more selected from the group consisting of nickel cobalt lithium manganate ternary positive electrode materials, lithium manganate positive electrode materials, lithium cobaltate positive electrode materials, nickel manganate lithium positive electrode materials, nickel acid lithium positive electrode materials, nickel cobalt aluminum ternary positive electrode materials, nickel cobalt manganese aluminum quaternary positive electrode materials, lithium manganese-rich positive electrode materials and lithium iron phosphate positive electrode materials; and / or, the solid electrolyte includes a combination of one or more selected from the group consisting of sulfide solid electrolytes, oxide solid electrolytes, halide solid electrolytes and polymer solid electrolytes; further, the oxide solid electrolyte includes a combination of one or more selected from the group consisting of LiPON and its homologues, LLZTO and its homologues, LATP and its homologues; the sulfide solid electrolyte includes a combination of one or more selected from the group consisting of LGPS and its homologues, LiPSCl and its homologues, β-Li3PS4 and its homologues, Li7P3S 11 and its homologues, Li 10 GeP2S 12 and its homologues and a combination of one or more of Li6PS5X and its homologues, X is Cl, Br or I; the halide solid electrolyte comprises a combination of one or more selected from Li3InCl6 and its homologues, Li3YCl6 and its homologues; and / or the conductive agent comprises conductive carbon powder, and the conductive carbon powder comprises a combination of one or more selected from carbon black, conductive graphite, carbon fiber, carbon nanotubes and graphene.

10. The solid-state battery positive electrode material according to claim 1, characterized in that: The molecular weight of the binder is 800,000 to 10 million; the binder includes a combination of one or more selected from polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, polyphthalamide, polyamide-imide, polyvinyl alcohol, polyetherimide, and polyimide; and / or, in terms of mass percentage, the binder accounts for 0.01% to 10% of the raw material of the positive electrode material.

11. The solid-state battery positive electrode material according to claim 10, characterized in that: The molecular weight of the binder is 2 million to 5 million; and / or, in terms of mass percentage, the binder accounts for 0.05% to 5% of the raw material of the positive electrode material.

12. The solid-state battery positive electrode material according to claim 1, characterized in that: The viscosity of the binder is 100 to 8000 cps; and / or the particle size of the solid electrolyte is 0.1 to 20 microns; and / or, in terms of mass percentage, the solid electrolyte accounts for 5% to 45% of the raw material of the positive electrode material; and / or, in terms of mass percentage, the positive electrode active material accounts for 50% to 90% of the raw material of the positive electrode material; and / or, in terms of mass percentage, the conductive agent accounts for 1% to 40% of the raw material of the positive electrode material.

13. The solid-state battery positive electrode material according to claim 12, characterized in that: The viscosity of the binder is 1000-5000 cps; and / or the particle size of the solid electrolyte is 0.1-5 microns; and / or, in terms of mass percentage, the solid electrolyte accounts for 10%-35% of the raw material of the positive electrode material; and / or, in terms of mass percentage, the positive electrode active material accounts for 60%-85% of the raw material of the positive electrode material; and / or, in terms of mass percentage, the conductive agent accounts for 2%-20% of the raw material of the positive electrode material.

14. A method for preparing a solid-state battery positive electrode material according to any one of claims 1 to 13, characterized in that: The preparation method comprises: The positive electrode active material, the solid electrolyte and the conductive agent are mixed for the first time, and after being ground evenly, a molding aid is added for the second mixing, and then a binder is added for the third mixing, and the mixture is pressed and molded to obtain the solid-state battery positive electrode material.

15. The method for preparing a positive electrode material for a solid-state battery according to claim 14, characterized in that: The compression molding is performed at a temperature of 20 to 200° C. and a pressure of 100 to 1000 MPa; further, at a temperature of 30 to 100° C. and a pressure of 300 to 500 MPa.

16. A solid-state battery, comprising a positive electrode sheet, characterized in that: The positive electrode sheet comprises the solid-state battery positive electrode material according to any one of claims 1 to 13.

17. The solid-state battery according to claim 16, characterized in that: The operating pressure of the solid-state battery is less than 50 MPa, further less than 30 MPa, and further 1 to 10 MPa.

Citation Information

Patent Citations

  • Positive electrode slurry, preparation method thereof, electrode sheet, preparation method thereof and lithium ion battery

    CN109192980A

  • High-power all-solid-state battery and preparation thereof

    CN111082128A

  • Dry method for preparing lithium battery positive and negative plates

    CN112420986A

  • All-solid-state lithium ion battery and preparation method thereof

    CN116314654A

  • Electrode plate as well as preparation method and application thereof

    CN116525760A